Experimental Innovations in Surface Science A Guide to Practical Laboratory Methods and Instruments - Yates Jr., John T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book is a new edition of a classic text on experimental methods and instruments in surface science. It offers practical insight useful to chemists, physicists, and materials scientists working in experimental surface science. This enlarged second edition contains almost 300 descriptions of experimental methods. The more than 50 active areas with individual scientific and measurement concepts and activities relevant to each area are presented in this book. The key areas covered are: Vacuum System Technology, Mechanical Fabrication Techniques, Measurement Methods, Thermal Control, Delivery of Adsorbates to Surfaces, UHV Windows, Surface Preparation Methods, High Area Solids, Safety. The book is written for researchers and graduate students.
Vacuum System Technology -- Mechanical Fabrication Techniques -- Measurement Methods -- Thermal Control -- Delivery of Adsorbates to Surfaces -- UHV Windows -- Surface Preparation Methods -- High Area Solids -- Safety.
Keywords: Surfaces (Physics).; Interfaces (Physical sciences).; Thin films; Materials—Surfaces.; Physical chemistry; Microwaves; Optical engineering; Surface and Interface Science, Thin Films; Surfaces and Interfaces, Thin Films; Physical Chemistry; Microwaves, RF and Optical Engineering